The 5-HTTLPR-rs25531 S-A-S-A Haplotype and Chronic Stress Moderate the Association Between Acute Stress and Internalizing Mental Disorders Among HIV+ Children and Adolescents in Uganda - Kalungi, Allan; Womersley, Jacqueline S.; Kinyanda, Eugene; Joloba, Moses L.; Ssembajjwe, Wilber; Nsubuga, Rebecca N.; Seedat, Soraya; Hemmings, Sian M. J. (Frontiers in Genetics, 2021)
Background Internalizing mental disorders (IMDs) among HIV+ children and adolescents are associated with poor disease outcomes, such as faster HIV disease progression. Although it has been suggested that the development of IMDs is moderated by interaction of stressful life events and vulnerability factors, the underlying etiology is largely unknown. Serotonin transporter gene (solute carrier family 6 member A4, SLC6A4) and human tryptophan hydroxylase 2 gene (TPH2) polymorphisms have been implicated in the development of IMDs. This study investigated the association between acute stress and IMDs, and moderation by chronic stress and genetic variants in SLC6A4 and TPH2. Hypothesis Acute stress acts through genetic and environmental vulnerability factors to increase the risk of developing IMDs. Methods Polymorphisms in SLC6A4 (5-HTTLPR, rs25531, 5-HTTLPR-rs25531 and STin2 VNTR) and TPH2 (rs1843809, rs1386494, rs4570625 and rs34517220) were genotyped in 368 HIV+ children and adolescents (aged 5-17 years) with any of the IMDs (depression, anxiety disorders or post-traumatic stress disorder), and 368 age- and sex-matched controls who were also HIV+. Chronic and acute stress categories were derived by hierarchical cluster analysis. Logistic regression analysis was used to assess the independent moderating effect of chronic stress and each selected polymorphism on the association between acute stress and IMDs. Results We observed a statistically significant association between severe acute stress and IMDs (p = 0.001). Children and adolescents who experienced severe acute stress were twice as likely to develop IMDs compared to children and adolescents who experienced mild acute stress (p = 0.001). Chronic stress interacted with severe acute stress to increase the risk of IMDs (p = 0.033). Acute stress was found to interact with 5-HTTLPR-rs25531 S-A-S-A haplotype to increase the risk for IMDs among Uganda HIV+ children and adolescents (p = 0.049). We found no evidence for a combined interaction of acute stress, chronic stress and 5-HTTLPR-rs25531 on IMDs. Conclusions The odds of having an internalizing mental disorder were higher among HIV+ children and adolescents who experienced severe acute stress compared to HIV+ children and adolescents who experienced mild acute stress. Chronic stress and 5-HTTLPR-rs25531 independently moderated the association between acute stress and IMDs.